A Review on Sea Shells Waste as Partial Replacement of Fine Aggregate in Concrete - Zaimy, Nurnajihah; Prof Madya Ir. Ts. Dr. Abdul Halim bin Abdul Ghani (Recent Trends in Civil Engineering and Built Environment, 2023)
Fast development in the recent years has increased the demand of natural fine aggregate to be used in construction industry and has made the construction industries in crisis to find a good alternative to handle this problem. Million tons of waste materials appear and was dumped untreated at the open fields or landfills leading to serious environmental problems could be investigated for their potential to be used as partial replacement of fine aggregate in concrete production. Different type of waste products such as fly ash, tobacco waste and rice husk has been used in the previous studies to determine the effectiveness of their use as a substitute of fine aggregate in producing the concrete. In this research, the partially displacement of different types of seashells as fine aggregate was analyzed and discussed based on the result from the previous research. The aim of this study is to determine the optimum percentage of seashells as a replacement of fine aggregates and to investigate the effect of concrete containing seashells as a partial fine aggregate replacement towards density, compressive strength and splitting tensile strength of concrete. Hence, by incorporating the different types of sea shells for replacing fine aggregates would reduce the cost of the construction and the amount of sea shells disposal also can be reduced. Thus, it will create a clean environment and can reduce the demand of natural fine aggregates in future. The optimum percentage for cockle shell is 5% to 10%, for oyster shell is 20%, for scallop shell is 5% and 0% to 100% for seashells as replacement of fine aggregate in concrete work because it gives the highest value for compressive strength test compared to the other percentages.